Disorientasi Fungsi: Eksistensi Lembaga Adat Dayak Meratus di Desa Bangkalan Dayak Kabupaten Kotabaru - Rifani, Muhammad; Budhi , Setia (Huma: Jurnal Sosiologi, 2026)
The existence of customary institutions is a vital instrument in sustaining the lives of indigenous communities based on ancestral cultural values. This study aims to analyze the existence of customary institutions in carrying out their roles and functions within indigenous societies. The research employs a qualitative case-study approach. Data were collected through observation, interviews, and documentation, and analyzed using the Manual Data Analysis Procedure (MDAP). The findings indicate that customary institutions continue to perform important functions in social life, particularly in regulating the implementation of customary rituals, maintaining social order, and serving as sources of reference for norms and cultural values. However, within cultural dynamics influenced by social change, customary institutions also experience signs of dysfunction, such as a weakened role in environmental management and declining participation among younger generations due to limited knowledge and adaptive capacity. These findings emphasize that the existence of customary institutions is dynamic, capable of generating positive impacts in maintaining identity and social cohesion, yet also potentially producing negative effects if not accompanied by capacity strengthening and role renewal in accordance with contemporary social contexts. This study contributes to the development of sociological knowledge, particularly within the framework of structural functionalism. It further recommends that customary institutions, indigenous communities, and village governments more effectively implement the substantive values of indigenous cultural traditions to maintain ecological balance and preserve the identity of the Dayak Meratus indigenous community.